FORMATION OF THE ORGANIZATIONAL AND ECONOMIC MECHANISM AND STRATEGIES FOR SAFE INNOVATIVE DEVELOPMENT OF SOCIO-ECONOMIC SYSTEMS - NYZHNYK, Oleh; NYZHNYK, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2024)
On the basis of the analysis of scientific approaches to the construction of the management mechanism of socio-economic systems, the most typical ones for the modern development of the economy of Ukraine are highlighted. Strategies and mechanisms for the implementation of innovative development of socio-economic systems are closely related to the development of high-tech production, the creation of innovative products, the development of innovation and investment potential, the provision of safe development of socio-economic systems during a prolonged state of war, in view of the support of highly developed European countries. Based on the intended directions of the strategy for the development of innovative activity for the future, emphasis is placed on innovative active forms and mechanisms of ensuring socio-economic systems. The main components of the mechanisms of safe innovative development and their interdependence and interaction are defined. The formation of any organizational and economic mechanism for the innovative development of socio-economic systems, as a set of states and processes that make up any management system, should take place on the basis of combining into one system the constituent elements and various variants of their interrelationships, the set of which should form the state and content of innovative processes taking place in the socio-economic system or in the environment of its functioning. The proposed procedure for the formation of an organizational and economic mechanism and strategies for the safe innovative development of socio-economic systems will allow, at the level of strategic planning of their innovative development, to determine the prospects and effectiveness of the introduction of innovative projects or scenarios of safe development, monitor the implementation of the innovative development strategy, evaluate and adjust the proposed strategies and develop directions for further innovative development of socio-economic systems.
Keywords: mechanisms and strategies of innovative development; security policy; socio-economic systems